Analisis Pengaruh Boikot Produk Kopi Starbucks terhadap Peningkatan Minat Beli Kopi Lokal pada Gen Z di Indonesia - Dessy Dwiyanti (Jurnal Ekonomi Manajemen Akuntansi, 2024)
Regarding the socio-political conflict between Israel and Palestine, many countries have criticized Israel's actions by boycotting Israeli products and products that support Israeli aggression against Palestine. Starbucks products are one of the products that support Israeli aggression and are very closely related to Gen Z in Indonesia, so this study was performed to examine the impact of a boycott of Starbucks products on interest in buying local coffee products among Gen Z using quantitative methods, because previous similar research was carried out using qualitative methods. A total of 100 Gunadarma University students were respondents to fill out this research questionnaire. The data analysis technique used is hypothesis testing through simple regression analysis assisted by SPSS software. The conclusion drawn from hypothesis testing showed an influence between the effect of boycotting Starbucks products (X) and the interest in buying local coffee (Y).